KONTRIBUSI UJI KOMPETENSI CALON PENGAWAS MADRASAH TERHADAP PENGEMBANGAN INSTRUMEN SUPERVISI MANAJERIAL - Nana Umar Sumarna (Tatar Pasundan: Jurnal Diklat Keagamaan, 2018)
Research in the field of madrasah supervisors is still very lacking, this study fills the less space. The problem of this research is whether the competency test of madrasah supervisor candidate conducted by the Regional Office of the Ministry of Religion of West Java Province has contributed to the development of managerial supervision instruments in the training of the formation of candidates for supervisors of madrasah conducted at BDK Bandung 2015. For the purposes of this study, case study research and as data analysis techniques used simple regression. Anova results show the value of Foutpit = 4.41 while refear table with dk = 1, and df = 69 with 95% confidence level of 3.99. Therefore it can be said that Foutput 4.41 Ftabel  3.34, so H0 rejected and H1 accepted or in other words competence test of candidate supervisor of madrasah have contribution to development of instrument of managerial supervision. The amount of competency test contribution to the development of managerial supervision instrument can be seen from the regression equation Ŷ = 49.77 + 0.26 X. From the regression equation it can be concluded that, every one point increase in competency test will contribute as much as 0.26 points against the development of the instrument managerial supervision. In addition, the supervisory competence test also has a relationship with the correlation coefficient (r=0.247) with the development of managerial supervision instruments. Key words: madrasah supervisor, instrument development, managerial supervision, competency test.